POST-CHARISMATIC ISLAM: DIGITAL MEDIATION, HERMENEUTICAL INNOVATION, AND PARTICIPATORY DEMOCRACY IN SOUTHEAST AND CENTRAL ASIA - Muhammad Sukri (UIN Mataram, 2026)
The transformation of Islamic authority in the digital age represents a critical juncture in the Muslim world's engagement with modernity. This study examines the post-charismatic condition characterized by the routinization of authority away from individual leaders toward institutional and algorithmic systems through an integrated analysis of hermeneutical innovation, moral philosophy, and political practice. Using Critical Synthesis methodology grounded in contextual critical historical inquiry and analysis (CCHIA), we investigate three interconnected domains: (1) the Ma'na-cum-Maghza hermeneutical framework for Qur'anic interpretation; (2) the integration of classical Islamic moral philosophy into contemporary education; and (3) the divergent trajectories of political transformation in Indonesia and Central Asia. Our findings reveal that successful post-charismatic transitions depend on what we term 'reflective-critical' civil society engagement, which balances spiritual depth with democratic responsiveness. The Indonesian case of Lakpesdam NU demonstrates how religious communities can foster participatory democracy through multi-layered communication strategies, while Central Asian contexts illustrate the risks of 'reconstituted charisma' in the absence of such institutional safeguards. We argue that the future of Islam in the digital age hinges on the ummah's capacity to synthesize classical scholarly traditions with the affective and epistemological demands of technologically mediated publics. This article contributes to Islamic studies and political science by mapping the theoretical and practical dimensions of post-charismatic authority in the context of digital globalization.